GAMBARAN STIGMATISASI DAN DISKRIMINASI TERHADAP PENDERITA TUBERKULOSIS (TB) PARU DI KELURAHAN SIDOMULYO BARAT PEKANBARU - Nurwahidah "; Suyanto "; Siti Mona Lestari Amelia Lestari (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Tuberculosis ( TB ) is a major cause of death. The decrease in morbidity and mortality due to TB in Indonesia still have not achieved the national target. Lack of achievement is influenced by several factors, one of which is the stigma and discrimination against peoples with pulmonary TB. Peoples with TB often make or get stigma and discrimination. This will contribute to delay diagnosis of TB and reduce patient compliance in the treatment of TB. Stigma and discrimination can be sourced from himself and others. This type of research is descriptive qualitative approach with in-depth interviews, focus group discussions, and observations. By using snowballing sampling technique 21 samples obtained from patients with pulmonary TB population, patient families, communities and health service. The results obtained are the discovery of stigma and discrimination against peoples with pulmonary TB from himself, families and cummunities. Stigma found in this study is a lot, especially the stigma of communities. Stigma obtained the notion that TB is very contagious until treatment is completed, due to the habit of smoking, can be transmitted only to the person who has the same blood type with the patients, face to face with patients is dangerous, people who contract TB will not live long or will soon be death, people who live in a dirty environment will be more easily infected with TB, the TB bacteria will not disappear from the eating utensils and drinking patients if just washed away. And discrimination are emerging that excessive use of masks, separation bed with him wife, avoid people with TB, separation equipment eating and drinking, and did not want to treat people with TB.Key words: Tuberculosis, stigmatization, discrimination